Delayed Bochdalek Diaphragmatic Hernia Appearance and Coincidence with Pneumonia in One-Year-Old Baby: A Case Report - Imil Irsal Imran; Finny Fitry Yani; Riki Alkamdani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Congenital diaphragmatic hernia (CDH) is a developmental defect in the diaphragm leading to protrusion of abdominal contents into the thoracic cavity. The incidence rates showed that this disease happened to one in 2,200-3,000 births. This study aimed to describe a case of delayed Boschdalek diaphragmatic hernia and coincidence with pneumonia in a one-year-old baby. Case Presentation: A 12-month-old girl came to the emergency room of Dr. M. Djamil General Hospital with a chief complaint of breathlessness for 2 days before admission to the hospital. She had difficulty gaining weight, only about 200 grams per month. The symptoms are breathlessness, cyanosis, asymmetry of lung sounds, change in the position of the heart sound, and scaphoid abdomen. The chest X-ray showed the opacity loops, which are fluid-filled, suggestive left diaphragmatic hernia. Conclusion: Pneumonia-like symptoms and signs could be an initial or coincidence with delayed presentation of Bochdalek hernia diaphragmatic.